2018
DOI: 10.23850/22565035.938
|View full text |Cite
|
Sign up to set email alerts
|

Validación de un método analítico mediante espectrofotometría UV/VIS, para la cuantificación de formaldehído libre en textiles y aplicación en el análisis de prendas comercializadas en el mercado colombiano

Abstract: El formaldehído ha sido reportado como cancerígeno por la Agencia Internacional para la Investigación del Cáncer (IARC), también se ha reportado que niveles bajos de formaldehído pueden producir irritación en la piel, los ojos, la nariz. El formaldehído, se emplea como componente en resinas, en tejidos de algodón como producto de acabado antiarruga y antiencogimiento. En el mercado textil colombiano, este tipo de sustancias tóxicas no son controladas. En este trabajose validó un método analítico mediante espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Ten of them exceeded the threshold value of 75 mg/kg, with a maximum of 206.1 mg/kg [ 30 ]. In 2018, Caro Zapata et al [ 53 ] found formaldehyde in 74% of the analysed samples in Colombia, reporting a maximum concentration of 87 mg/kg. These levels were similar to those found by Aldag et al [ 23 ], who reported a maximum level 75.9 mg/kg in several T-shirts and pants purchased in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Ten of them exceeded the threshold value of 75 mg/kg, with a maximum of 206.1 mg/kg [ 30 ]. In 2018, Caro Zapata et al [ 53 ] found formaldehyde in 74% of the analysed samples in Colombia, reporting a maximum concentration of 87 mg/kg. These levels were similar to those found by Aldag et al [ 23 ], who reported a maximum level 75.9 mg/kg in several T-shirts and pants purchased in Germany.…”
Section: Discussionmentioning
confidence: 99%